1996
DOI: 10.1111/j.1365-2958.1996.tb02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the transcriptional arrangement of Azotobacter vinelandii alginate biosynthetic genes: identification of two independent promoters

Abstract: The study of alginate biosynthesis, the exopolysaccharide produced by Azotobacter vinelandii and Pseudomonas aeruginosa, might lead to different biotechnological applications. Here we report the cloning of A. vinelandii algA, the gene coding for the bifunctional enzyme phosphomannose isomerase-guanosine diphospho-o-mannose pyrophosphorylase (PMI-GMP). This gene was selected by the complementation for xanthan gum production of Xanthomonas campestris pv. campestris xanB-mutants, which lack this enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Effect of mucA, mucABCD, and mucC mutations on algD transcription. Most of the molecular genetics analysis of alginate production in A. vinelandii has been carried out in the highly mucoid strain ATCC 9046 (6,7,24,26,30,31,34,35,36). The detailed analysis of the structure of the regulatory region of the AEIV algD gene is currently being performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of mucA, mucABCD, and mucC mutations on algD transcription. Most of the molecular genetics analysis of alginate production in A. vinelandii has been carried out in the highly mucoid strain ATCC 9046 (6,7,24,26,30,31,34,35,36). The detailed analysis of the structure of the regulatory region of the AEIV algD gene is currently being performed.…”
Section: Resultsmentioning
confidence: 99%
“…In A. vinelandii, the biosynthetic gene cluster is arranged in three operons, one of which transcribes the algD gene alone (6,24,30), while in the latter bacterium, this gene cluster is transcribed as a single operon, whose transcription is started from a promoter upstream of the algD gene (9). The alternative sigma factor E (also known as AlgU or AlgT) is responsible for the transcription of the algD gene in P. aeruginosa (44), as well as in Pseudomonas syringae (21).…”
mentioning
confidence: 99%
“…All genes involved in bacterial alginate biosynthesis, except algC (20), are clustered on the chromosome and are transcribed in one or several units (6,8,34,36). Polymerization of the sugar monomers takes place in the cytoplasmic membrane, using GDP-mannuronic acid as a precursor.…”
mentioning
confidence: 99%
“…Considering the enzymatic treatment of infections caused by biofilm-forming bacteria, a search was carried out for a new algL from soil bacteria [19] . Moreover, genetic studies on algL-producing microorganisms have revealed that the algL genes are clustered with other alginate biosynthetic gene loci [20] . Hence, in the present study and based on the presence of algL gene, an algL-producing bacterium named Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%